Manajemen Pers: Antara Idealisme dan Komersialisme - Taufik Akhyar (Intizar, 2015)
The results of a study evaluating on how ideal and organized the management of press. Besides, management as a science and art, and management functions were discussed. Then what and how the press and journalism, the press law and ethics perspective, and the functions of the press were also described. This article concludes that the press as an organization cannot be separated by the application of management, both as a science and an art in order to achieve the objectives. Then, the existence and dynamics of the press at this time cannot be separated with the past life of the press, the press in the pre-independence as a struggle-oriented tool, press in the era of independence that slowly leads to economic and social institutions that tend to forward commercialism and neglect idealism.  Moreover, the freedom of press cannot be interpreted as freedom to carry out journalistic activities freely, but these freedoms must be subject to the law and journalistic ethics. Therefore, a good press is a press that is able to manage the balance between the demands of idealism and commercialism.